La crisis del sistema político ecuatoriano y la caída de Gutiérrez - Paltán, Julio (2005)
This article analyzes the course of deslegitimación and declivity of the representative democratic system in Ecuador since the electoral triumph of authoritarian populism, corporative and clientelist government of Lucio Gutiérrez. In addition, it puts some elements that affect its overthrow, and that reflects a deficit of citizenship and national integration.